Subjective Well Being Profile of College Students - Kurniasari, Mitta; Astuti, Budi; Septi Purnama, Diana (International Journal of Applied Guidance and Counseling, 2025)
Subjective well-being is one of the variables that can describe how an individual's level of life satisfaction. Individuals who have a high level of subjective well-being tend to feel happy and satisfied with their lives. This study aims to analyze the subjective well-being profile of college students. The profile of well-being will be seen based on gender, age, and level. This research is a quantitative research with survey research type. Data were collected from 202 college students from various study programs and levels that were determined using accidental random sampling. Data were collected using a questionnaire and analyzed using quantitative descriptive statistics. The results showed an overview of the subjective well- being profile of college students in terms of gender, age, and level. This research can be used as preliminary research for further research on the subjective well-being of college students.